Spatial development of Russia: Does geography matter? - Evgeniya Kolomak (European Regional Science Association (ERSA), 2014)
We study the dynamics of inter-regional economic disparities for a number of development characteristics, test the hypothesis of the new economic geography and connect the results with the prediction of the bell curve describing spatial concentration over time. The results of our analysis suggest that the concentration of economic activity continues in Russia and that the pace of the interregional divergence is rather high. These findings bring us to the conclusion that the country rests at the left side of the bell-shaped relationship between interaction costs and spatial distribution. Both the western and eastern regions experience centripetal tendencies; however, despite predictions, no essential redistribution of the production factors and outputs from the East to the West is revealed. In other words, first nature (the East's natural resources and raw materials, which are highly valued in the global market) is balanced by second nature (the West's better infrastructure and large markets). The significant factors in spatial concentration and total productivity growth are density, the size of and access to markets and the diversity of the economy. Insensitivity to the diversification is specific to the eastern regions of Russia. There are also sectorial peculiarities: population density and proximity to markets negatively influences; due to the immobility of supply. External markets have no significant effect on construction. Due to fierce competition, sectorial specialization decreases both productivity and the rate of concentration. These results of the estimates are in accordance with the predictions of the new economic geography. One of the practical ideas suggested by this analysis is the conclusion that in the near future, we will observe further concentration of economic activity and interregional divergence in Russia. The forces behind the agglomeration economy and regional disparities are market-based (increasing returns to scale and imperfect competition), and they are beginning to play a major role in the country in the transition and in the post-transition period. Despite the active regional policy and the massive redistribution efforts undertaken by the central government, regional disparities continue to grow. The new economic geography theory describes the mechanisms of agglomeration and provides suggestions for the pro-dispersion forces to countervail centripetal tendencies. Translated into the language of the practical recommendations, they include essential improvement of transport and communication infrastructure, radical decreases in trade cost and the elimination of regional institutional barriers, as well as an active social policy supporting lagging regions.
Keywords: R12; O18; 330; regional disparities; economic geography; empirical estimates; Russia